A Ritual Of Finding Gonggong By Using Frying Oil At Busung Village Of Bintan Island In Riau Arhipelago Province - Dewi Murni (International Journal of English Linguistics, Literature, and Education (IJELLE), 2019)
Malay people are very well known of their local wisdom that expresses a message of Malay life condition, especially in Kepulauan Riau. One of the local tradition is finding gonggong by using frying oil. This tradition is one way to communicate and socialize the culture of Malay. The purpose of this research are to find out the function of the rite and to know the meaning of finding gonggong. This tradition is almost disappearing because many people do not practice this ritual to the next generation so that the researcher tried to identify it by interviewing the informant and joining the activity directly. By doing this activity, there are some function and meaning of finding gonggong which are used to preserved the culture of Malay especially in Bintan Island.